The influence of injection molding parameter on properties of thermally conductive plastic - Azis, N. Hafizah; Rahim, M. Zulafif; Sa’ude, Nasuha; Rafai, N.; Yusof, M.S.; Tobi, A.L.M.; Sharif, Z.M.; Ibrahim, M. Rasidi; Ismail, A.E. (IOP Publishing, 2017)
Thermally conductive plastic is the composite between metal-plastic material that is becoming popular because if it special characteristic. Injection moulding was regarded as the best process for mass manufacturing of the plastic composite due to its low production cost. The objective of this research is to find the best combination of the injection parameter setting and to find the most significant factor that effect the strength and thermal conductivity of the composite. Several parameter such as the volume percentage of copper powder, nozzle temperature and injection pressure of injection moulding machine were investigated. The analysis was done using Design Expert Software by implementing design of experiment method. From the analysis, the significant effects were determined and mathematical models of only significant effect were established. In order to ensure the validity of the model, confirmation run was done and percentage errors were calculated. It was found that the best combination parameter setting to maximize the value of tensile strength is volume percentage of copper powder of 3.00%, the nozzle temperature of 195oC and the injection pressure of 65%, and the best combination parameter settings to maximize the value of thermal conductivity is volume percentage of copper powder of 7.00%, the nozzle temperature of 195oC and the injection pressure of 65% as recommended.